Analysis of Multiple Factors Involved in Pertussis-Like Coughing. (June 2020) - Cao, Jiaying; Xu, Lu; Pan, Jiahua
Objectives . To identify risk factors associated with the prognosis of pertussis-like coughing. Methods . A retrospective study on children hospitalized with pertussis-like coughing from 2018 to 2019. We collected all the case data from medical records including age, gender, vaccination, clinical symptoms, complication, pathogens, white blood cell (WBC) count, lymphocyte ratio, application of macrolide antibiotics, usage of sulfamethoxazole, and usage of inhaled glucocorticoids. Logistic regression was used in this study. Results . A total of 213 hospitalized children with pertussis-like coughing were included in this study. About 70 children were cured within 2 weeks. One120 children were cured from 2 weeks to 3 months, including cases of initial attack and relapse. Symptoms lasting longer than 3 months accounts for 10.8%. Bordetella pertussis, WBC count >20 × 10 9 /L and lymphocyte ratio >60% were associated with poor prognosis ( P < .05). Conclusions. Bordetella pertussis, WBC count, and lymphocyte ratio are independent risk factors for poor prognosis.